LaPT2 Gene Encodes a Flavonoid Prenyltransferase in White Lupin - Liu, Jinyue; Xia, Yaying; Jiang, Wenbo; Shen, Guoan; Pang, Yongzhen (Frontiers in Plant Science, 2021)
Legume plants are rich in prenylated flavonoid compounds that play important roles in plant defense and human health. In the present study, we identified a prenyltransferase gene LaPT2 in white lupin (Lupinus albus), which shows high identity and close relationship with other known prenyltransferase genes involved in flavonoid prenylation in planta. The recombinant LaPT2 protein expressed in yeast cells exhibited relatively strong activity toward several flavonols (eg. kaempferol, quercetin and myricetin) and relatively weak activity toward flavanone (naringenin). In addition, the recombinant LaPT2 protein was also active toward several other types of flavonoids with distinct enzymatic affinities, including galangin, morin, 5-deoxyquercetin, 4'-O-methylkaempferol, taxifolin, and aromadendrin. LaPT2 gene was preferentially expressed in the roots, which is consistent with the presence of prenylated kaempferol in roots. Moreover, we found that the expression level of LaPT2 paralleled with those of LaF3H1 and LaFLS2 genes, relatively high in roots and low in leaves, suggesting that they were essential for the accumulation of prenylated kaempferol in roots. The deduced full-length LaPT2 protein and its signal peptide fused with GFP are targeted to plastids in Arabidopsis thaliana protoplast. Our study demonstrated that LaPT2 from white lupin is responsible for the biosynthesis of prenylated flavonoids, in particular flavonols, which could be utilized as phytoalexin for plant defense and bioactive flavonoid compounds for human health.